2003
DOI: 10.1080/03057920302587
|View full text |Cite
|
Sign up to set email alerts
|

Learning to be Violent: The role of the school in developing adolescent gendered behaviour

Abstract: This paper examines the role of the school, and of the peer group culture in particular, in constructing male and female identity among adolescents within the context of high levels of gender violence. It draws on a DfID-funded study into the abuse of girls in schools in three African countries (Zimbabwe, Malawi and Ghana). This study documents incidents of male teachers and older male pupils aggressively propositioning female pupils for sex, 'sugar daddies' preying on schoolgirls in the vicinity of the school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 10 publications
2
48
0
1
Order By: Relevance
“…Using natural observations, group interviews and autobiographical memories, he concludes that in the cases where this type of behaviour deteriorates into intimidation, aggression is used as a form of social control with which to maintain hierarchical boundaries between genders. The studies developed in an African context by Wood and Jewkes (2001) and Leach (2003), about the abusive behaviour of boys towards girls concur with this and are of special interest. They note that for boys, intimidation represents a way of gaining access to the opposite sex and is also strongly related to the proof of gender role and masculinity.…”
Section: Introductionmentioning
confidence: 73%
“…Using natural observations, group interviews and autobiographical memories, he concludes that in the cases where this type of behaviour deteriorates into intimidation, aggression is used as a form of social control with which to maintain hierarchical boundaries between genders. The studies developed in an African context by Wood and Jewkes (2001) and Leach (2003), about the abusive behaviour of boys towards girls concur with this and are of special interest. They note that for boys, intimidation represents a way of gaining access to the opposite sex and is also strongly related to the proof of gender role and masculinity.…”
Section: Introductionmentioning
confidence: 73%
“…The situation perpetuates unequal relations and differential behavioural patterns amongst learners of different genders, in which the male dominates (Dunne 2007). The suggestion would simply be that male learners are expected to exhibit dominant and sexually violent behaviour while female learners are expected to be tolerant and submissive (Leach 2003). Being a female with mild intellectual disability worsens the situation, because they rarely receive treatment equal to their counterparts without disability because of common assumptions that they are unable to tell right and wrong, and that they cannot be credible witnesses (Balogh et al 2001) As revealed by Human Rights Watch (2001), the problem could push females into dropping out from school and/or absenteeism as a strategy to evade the problem, and thus further undermine their chances of accessing the curriculum on the same level as their male counterparts.…”
Section: Discussionmentioning
confidence: 96%
“…Bullying, like other forms of aggression, vary across cultures and contexts (McConville & Cornell, 2003). Sociological theorists assert that school norms can perpetuate inequality, alienation, aggression, and oppression among the students in relation to their race/ethnicity, gender, and socioeconomic background (Leach, 2003). Further, as youth bullying becomes understood within the realm of public health, greater attention is being paid to the impact of state laws on school safety especially for LGBT and sexually diverse youth.…”
Section: Macrosystemmentioning
confidence: 99%